Conformational dynamics of the F1-ATPase β-subunit: A molecular dynamics study - Böckmann, Rainer; Grubmüller, Helmut (Biophysical Journal, 2003)
According to the different nucleotide occupancies of the F(1)-ATPase beta-subunits and due to the asymmetry imposed through the central gamma-subunit, the beta-subunit adopts different conformations in the crystal structures. Recently, a spontaneous and nucleotide-independent closure of the open beta-subunit upon rotation of the gamma-subunit has been proposed. To address the question whether this closure is dictated by interactions to neighbored subunits or whether the open beta-subunit behaves like a prestressed "spring," we report multinanosecond molecular dynamics simulations of the isolated beta-subunit with different start conformations and different nucleotide occupancies. We have observed a fast, spontaneous closure motion of the open beta(E)-subunit, consistent with the available x-ray structures. The motions and kinetics are similar to those observed in simulations of the full (alpha beta)(3)gamma-complex, which support the view of a prestressed "spring," i.e., that forces internal to the beta(E)-subunit dominate possible interactions from adjacent alpha-subunits. Additionally, nucleotide removal is found to trigger conformational transitions of the closed beta(TP)-subunit; this provides evidence that the recently resolved half-closed beta-subunit conformation is an intermediate state before product release. The observed motions provide a plausible explanation why ADP and P(i) are required for the release of bound ATP and why gamma-depleted (alpha beta)(3) has a drastically reduced hydrolysis rate.